State-owned enterprise reform in Vietnam : lessons from Asia - Ng, Chee Yuen, ed (Singapore : Institute of Southeast Asian Studies, 1996)
"Paper originally presented to an Indochina Roundtable on "State-Owned Enterprises (SOEs) Reforms and Restructuring in Vietnam: lessons from Japan and Sotheast Asia," organized by the ISEAS, on 4-5 September 1995.
Keywords: Government business enterprises -- ASEAN countries -- Congresses; Government business enterprises -- Japan. -- Congresses; Government business enterprises -- Vietnam -- Congresses; Structural adjustment (Economic policy) -- Vietnam -- Congresses